From Coins to Code: An Islamic Monetary Perspective on the Rise of Digital Assets - Abdullah Shakir (Social Science Review Archives, 2025)
As digital finance continues to develop at an unprecedented rate, old questions regarding its purpose and palm have become even more important. This research investigates crypto assets from the perspective of Islamic monetary principles looking at the intellectual and juristic trail ''from Dinar to Digital.'' The classical Islamic scholarship of money was grounded in stability and intrinsic value along equitable exchange, and wealth protection (ḥifẓ al-māl). Such underpinnings, refined around gold, silver, and fulus, constitute the benchmark from which to assess the current realities of currency in the stabilization of value. This issue focuses particularly on the value of money in the classical Islamic scholarship, and the concepts of ribā, gharar, thamanīyyah, and māliyyah, to digital assets in their decentralized forms. Five of the most important classical positions on the nature of currency that simply is not gold or silver (conventional money). These have been studied to understand for us the classical positions on cryptocurrency to contemporary. This research draws from fiqh and classical monetary theory. To study these assets the study has divided them into four Main classes of digital assets: exchange-utility tokens, asset-backed stable coins, and algorithms. The study settles to the conclusion that no single classical categorization fully accommodates this asset class. It further recommends certain criteria for potential Shari‘ah recognition of digital assets that include, but are not limited to, degree of transparency, asset-linkage, systemic stability, and avoidance of hyper-speculation. This research seeks to enrich the contemporary debate to harmonize Islamic monetary heritage and finance and technology.